Pathogens Affecting the Reproductive System of Camels in the United Arab Emirates - Hassan Taha, Tariq (2011)
Brucella species, BVDV and BHV-1 are important worldwide pathogens that primarily infect cattle and other ruminants and are associated with serious economic impact to the animal production sector. Camels are indispensable domesticated animals for the people of desert areas, such as the Arabian Peninsula, and share the same environment and pasture with cattle, goats, sheep and other ruminants, which increase the likelihood of exposure to these pathogens. The investigation presented in this thesis was a serological survey conducted in Al-Ain region of the United Arab Emirates (UAE), and was designed to determine the presence of antibodies against Brucella species, BVDV and BHV-1. Serum samples from 812 camels of both sexes, and different ages were collected from the local central abattoir, the camel market and 10 private farms. A commercial competitive ELISA was used to determine the presence of Brucella abortus antibodies, and a blocking ELISA, was used for the detection of antibodies to BVDV and BHV-1. Samples with suspected or non-specific positive results, were retested with confirmatory tests such as Complement Fixation and Virus Neutralization test, as required. No sera from the 812 camels in this study tested positive for any of the three pathogens. Without underestimating the progress and efforts of the local veterinary authorities, these results indicate the need for more extensive sampling and comprehensive surveys on a systematic epidemiological basis and including other pathogens. It is also necessary to reconsider the criteria for performance and validation of the assays used. This will lead to a better understanding of the pathogenesis of the agents involved, and consequently enhance knowledge to improve existing control and eradication programmes of infectious diseases in camels.